CLEARED (Chemicals and Litmus testing with Effective Alkaline Range for Eye Damage): A Prospective, Interventional Study. (2nd November 2018) - Breazzano, Mark P.; Day, H. Russell; Tanaka, Sarah; Tran, Uyen
Abstract: Objectives: While immediate diagnosis and irrigation is standard chemical eye burn practice, it is unknown to what extent specific pH measurements influence management, given the frequent clinical availability of narrow‐spectrum nitrazine pH strips. We hypothesize that exclusive broad‐spectrum pH strip implementation leads to more accurate measurement and expedited ophthalmologic consultation. Methods: At a Level I trauma center over 25 months, all emergent adult ophthalmology consultations for chemical burns were included in a pre‐intervention ( n = 22) and post‐intervention ( n = 20) study design. During this time, narrow‐spectrum nitrazine pH strips available to non‐obstetric emergency department (ED) staff were exclusively replaced by broad‐spectrum strips. Causative chemical, time from triage to ophthalmology consultation, examination findings, ocular pH by ED and ophthalmology staff, and irrigation quantity were analyzed. Results: Most burns were alkaline. Time from triage (p = 0.043) and irrigation quantity following consultation (p = 0.047) each decreased following exclusive ED implementation of broad‐spectrum pH strips. There was greater pH congruence between consulting and primary physicians after intervention (p = 0.03). Conclusions: Exclusive non‐obstetric implementation of broad‐spectrum pH strips may allow greater accuracy and faster management of ocular chemical burns. Availability of narrow‐spectrum pH strips may be dangerous clinically by falsely reassuring the examiner with inherent inaccuracy.